2016
DOI: 10.1016/j.cam.2015.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of European air quality by WRF–CMAQ models using AQMEII-2 infrastructure

Abstract: h i g h l i g h t s• The model inter-comparison initiative AQMEII is outlined.• The NIMH's WRF-CMAQ model system as designed for AQMEII-2 exercise is described. • Simulations for 2010 over Europe as prepared for the ENSEMBLE tool are described. • O3, NO2 and PM model results are analyzed against surface measurements in ENSEMBLE. a b s t r a c tThe air quality modeling system WRF-CMAQ was applied to the European domain for the year 2010 in the frame of the Air Quality Model Evaluation International Initiative (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…CMAQ and CAMx photochemical models have been used with various objectives like the behaviour of plume rise, aerosols property and prediction of pollutant concentration. In most of the cases, CMAQ underestimates as compared to observation for AOD, ozone, PM 2.5 and PM 10 concentration while overprediction for O 3 (Hogrefe et al, 2014;Syrakov et al, 2015). AERMOD has been compared with ADMS-Urban and CALPUFF and results show AERMOD has lower as well as higher correlations than these models with various case studies.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…CMAQ and CAMx photochemical models have been used with various objectives like the behaviour of plume rise, aerosols property and prediction of pollutant concentration. In most of the cases, CMAQ underestimates as compared to observation for AOD, ozone, PM 2.5 and PM 10 concentration while overprediction for O 3 (Hogrefe et al, 2014;Syrakov et al, 2015). AERMOD has been compared with ADMS-Urban and CALPUFF and results show AERMOD has lower as well as higher correlations than these models with various case studies.…”
Section: Resultsmentioning
confidence: 93%
“…The results of WRF-CMAQ were underestimated for AOD, ozone, PM 2.5 and PM 10 concentration (Hogrefe et al, 2014). Again, WRF-CMAQ was applied to European region for prediction of O 3 and other pollutants (Syrakov et al, 2015). Modelling results showed that model is over-predicting for O 3 and underpredicting for other pollutants compared to observed data.…”
Section: Comparison Of Wrf-cmaq Studymentioning
confidence: 92%
See 1 more Smart Citation
“…While high-resolution regional models (e.g. Liora et al, 2016;Syrakov et al, 2016;Galmarini et al, 2017;Hong et al, 2017) and more complex downscaling methodologies (e.g. Milionis and Davies, 1994;Kumar and Goyal, 2016) than the one used here might, in theory, yield better results (Thunis et al, 2016), computational constraints make their application to climate timescales and continent-wide studies challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Deterministic models, such as chemistry transport models and high-resolution regional air quality models, compute pollutant concentrations as explicit functions of meteorological parameters, chemical transformation processes and source characteristics, and can consequently be computationally expensive (e.g. Liora et al, 2016;Syrakov et al, 2016;Hong et al, 2017). Statistical models are instead based on the relationship between observed small-scale variables (predictands) and large-scale fields from a numerical model (predictors), and are generally computationally inexpensive (Wilby et al, 2004).…”
Section: Introductionmentioning
confidence: 99%